2002
DOI: 10.1055/s-2002-34887
|View full text |Cite
|
Sign up to set email alerts
|

Baylis-Hillman Chemistry in Aqueous Media: A Fast and Practical Approach to the Azides of Baylis-Hillman Adducts in Solution and on Solid Phase

Abstract: Fast and practical access to azides of Baylis-Hillman adducts, from the corresponding acetates in aqueous media and in excellent yields is described. The solution phase methodology has been successfully translated to the solid phase for applications toward combinatorial synthesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 0 publications
0
16
0
Order By: Relevance
“…With this consideration in mind, we prepared a variety of substituted 2‐(azidomethyl)‐3‐phenylpropenoates ( 1 a – 1 k ) according to the reported procedure,15, 16 and subjected them to 2.0 equiv of NBS and visible light irradiation (with a 45 W household fluorescent lamp) in dichloromethane (DCM) under argon atmosphere. The results are summarized in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…With this consideration in mind, we prepared a variety of substituted 2‐(azidomethyl)‐3‐phenylpropenoates ( 1 a – 1 k ) according to the reported procedure,15, 16 and subjected them to 2.0 equiv of NBS and visible light irradiation (with a 45 W household fluorescent lamp) in dichloromethane (DCM) under argon atmosphere. The results are summarized in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…8 We selected azide 2f to optimize the reaction conditions (Scheme 1). Reduction of the ester group in 2f with diisobutylaluminum hydride smoothly produced the alcohol 3f stereoselectively as the E-isomer within 30 minutes.…”
Section: Synthesis Of 7-benzylidene-4678-tetrahydro[123]triazolomentioning
confidence: 99%
“…Synthesis of 7-benzylidene-4,6,7,8-tetrahydro [1,2,3]triazolo[5,1-c] [1,4]oxazepine: We initiated our study with the synthesis of allyl azides via an earlier reported procedure. 8 We selected azide 2f to optimize the reaction conditions (Scheme 1). Reduction of the ester group in 2f with diisobutylaluminum hydride smoothly produced the alcohol 3f stereoselectively as the E-isomer within 30 minutes.…”
mentioning
confidence: 99%
“…The procedure was the same as described in the preparation of 4a with 3d (0.99 g, 3 mmoles) except reaction time (7 hours 15, 52.56, 83.88, 89.13, 122.56, 127.97, 128.82, 129.03, 129.32, 132.74, 136.22, 142.44, 142.65, 167.13, 170.13; ms: m/z (%) 313 (M + , 16), 270 (100), 182 (16), 154 (15).…”
Section: Methyl 3-acetoxy-3-(2-ethynyl)phenyl-2-hydroxy-2-methyleneprmentioning
confidence: 99%
“…The reaction of adducts 2 a-d with acetic anhydride in the presence of catalytic amount of N , N-d i m e t h y laminopyridine (DMAP) in dichloromethane at room temperature gave the Baylis-Hillman acetate adducts 3a-d ( 7 6 -96%). The stereochemistry of the products was established by comparing NMR values of olefinic and methylene protons with literature values [15]. The stereochemistry of the products was established by comparing NMR values of olefinic and methylene protons with literature values [15].…”
mentioning
confidence: 99%